Avel·lí Artís i Balaguer (1881-1954), narrador - Fernández Poza, Óscar (Revista de lenguas y literaturas catalana, gallega y vasca, 2015)
En este artículo presento una faceta del editor, impresor y comediógrafo catalán Avel·lí Artís i Balaguer que no es mencionada dentro de las diferentes historias y monografías de literatura catalana, la de narrador. Se ordena el corpus de cuentos que hasta la fecha he localizado, publicados en diferentes revistas de la primera mitad del siglo XX, tanto en Cataluña como en el exilio. This article presents a facet of the editor, printer and comedy writer catalan Avel·lí Artís i Balaguer that is not mentioned in the different stories and case studies of Catalan literature, the narrator. Ordering the corpus of stories that have located so far published in different magazines in the first half of the twentieth century in Catalonia and in exile is ordered.